(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The object of research in this work is the mountain rivers of southern Kyrgyzstan. The purpose of the research is the geochemical assessment of industrial pollution of rivers as a result of anthropogenic and man-made impacts. To solve the tasks set, a literary review on the topic was conducted and water samples from the KaraDarya, Kok-Art, Kara-Unkur, Kurshab, and Zhazy rivers were selected. According to the results of laboratory tests, it was found that the content of chemicals in the samples did not exceed the norms of the established maximum permissible concentrations. It is proposed to implement a set of scientific and technical measures to reduce the negative impact of man-made factors.